Penggunaan Aplikasi Pegadaian Digital Service (PDS) Terhadap Transaksi Nasabah Pada PT. Pegadaian (PERSERO) UPC Ngrambe - Safitri, Kurniawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The Pegadaian Digital Service (PDS) application, launched by PT. Pegadaian in 2018, aims to facilitate customer transactions. Despite its potential, most customers at PT. Pegadaian UPC Ngrambe, who are predominantly elderly, do not understand or are uninterested in using the application. This study explores the impact of the PDS application on customer transactions and the level of assistance it provides. Using a quantitative research method and a questionnaire-based survey, 100 respondents were randomly selected. Data analysis conducted with SPSS version 29 revealed significant findings: the significance value (Sig.) of 0.006 is below 0.05, indicating a meaningful impact of application use on customer transactions. The t-test result (t count = 2.975 > 2.228) confirmed that application usage significantly influences customer transactions (X on Y). However, the effect size is relatively modest, contributing only 24% to the improvement of customer transactions, suggesting that other factors also play a role. This limited influence could be attributed to well-functioning traditional transactions and customers' limited digital literacy. The study recommends enhancing socialization efforts and providing targeted training, particularly for elderly users, to increase their understanding and usage of the PDS application, thereby maximizing its benefits for customer transactions.